Complete mitochondrial genome of blood pheasant (Ithaginis cruentus). (October 2013) - Zeng, Tao; Tu, Feiyun; Ma, Lele; Yan, Chaochao; Yang, Nan; Zhang, Xiuyue; Yue, Bisong; Ran, Jianghong
<x xml:space="preserve">Abstract</x> The blood pheasant Ithaginis cruentus belongs to the family Phasianidae and distributes in the eastern Himalayas, India, Nepal, Bhutan and China. In this study, the total mitochondrial genome of I. cruentus was firstly determined. The genome is 16, 683 bases in length. Bayesian inference, maximum likelihood and maximum parsimony methods were used to construct phylogenetic trees based on 12 concatenated protein-coding genes on the heavy strand. Phylogenetic analyses further confirmed that Ithaginis clearly diverged later than Arborophila, and Arborophila was a basal branch within Phasianidae.